Neoadjuvant chemotherapy followed by radical surgery in locally advanced vulvar carcinoma: a single-institution experience. Issue 5 (October 2022) - Adorni, Marco; Bazzurini, Luca; Lissoni, Andrea Alberto; Vecchione, Francesca; Negri, Serena; Grassi, Tommaso; Buda, Alessandro; Landoni, Fabio
Background: Squamous cell carcinoma of the vulva is a rare malignancy that affects elderly women. About one-third of vulvar cancers are diagnosed in an advanced stage, requiring extensive surgery. Neoadjuvant chemotherapy (NACT) has been introduced to reduce local tumor burden. In this retrospective study, we analyze the efficacy and toxicity of NACT followed by radical surgery. Methods: Patients with locally advanced vulvar cancer (LAVC) treated at our institution with neoadjuvant platinum and paclitaxel-based chemotherapy ± ifosfamide followed by surgery at our institution were retrospectively identified. Results: Fourteen patients (93%) completed NACT with tolerable toxicities (G3–G4 toxicity: 30%). Thirteen patients (87%) underwent surgery. The overall clinical response rate on vulvar disease was 66% (20% complete response, 46% partial response), confirmed by histopathologic analysis, while on inguinal lymph nodes it was 69% (23% complete response, 46% partial response). At the pathologic examination, all patients had negative surgical margins. Three out of 9 patients (33%) with lesions infiltrating the urethral meatus and 4 patients out of 7 (57%) with anal involvement did not require urethral amputation or colostomy, respectively, after NACT. No severe postoperative complications were described. Overall survival at 5 years was 60%, and median overall survival was 76 months. Conclusion: NACT followed by surgery in locally advanced vulvar cancer is well tolerated and allows surgical modulation.